Structural Model of the Relationship between Professional Competence of Teachers and Self-Directed Learning of Students as Mediators of Students’ Achievement Motivation - mansoure hajhosseini; Halimeh Nafeie (مطالعات روانشناسی تربیتی)
The purpose of this study was to provide a structural model of the relationship between professional competence of teachers and self-directed learning of students as mediators of their Achievement Motivation. The research was conducted in a descriptive way through identifying the relationships between the variables by the form of causal model in the correlated research the design. For this purpose, a sample of 224 subjects was selected from the statistical population (N = 250) (female secondary school students of Turkmen city in the academic year of 2016-2017). They responded to three self-reporting tools, including of Williamson Self-directed Learning Scale (2007) and the Achievement Motivation test (ACMT) and the Modified professional competence of teachers Questionnaire (Karimi, 2009). Pearson correlation analysis was used for data analysis and the path analysis with maximum probability method was used In order to test the fitting of the hypothesized models and estimate the direct, indirect and total effects of the coefficients. The findings of the research showed a significant direct effect of the perception of the professional competence of teachers on self-directed learning of students and their Achievement Motivation. Also Research results confirm the mediating role of the Achievement Motivation among them. The findings of the research also provide a suitable fit of the proposed model. Based on this, students 'perception of professional competence of teachers was able to predict 41% of students' self-directed learning variance with the Achievement motivation.